Comparison of indirect immunofluorescence and membrane fluorescence assays for the differentiation of antibodies to human immunodeficiency virus types 1 and 2. - Gallo, D (1992)
Serum samples from 20 human immunodeficiency virus type 1 (HIV-1)- and 30 HIV-2-infected and 7 dually infected individuals were reacted by using the indirect immunofluorescence assay (IFA) and membrane fluorescence assay in order to determine whether these methods were useful for typing HIV-1 and HIV-2 antibodies. Although 41 of 50 (82%) of the HIV-1- and HIV-2-positive specimens cross-reacted to some extent with the heterologous antigen in the IFA, the antigen with the higher titer correlated completely with the infecting type. The IFA could not distinguish single from dual infections, however. In contrast, only 4 of the 50 (8%) serum samples cross-reacted in the membrane fluorescence test. All seven of the specimens from patients with mixed infections reacted with both antigens. The membrane fluorescence test appears to be reliable for serodifferentiation of HIV-1 and HIV-2 infections and may be useful for laboratories with low-volume typing requirements.